Porous ultra-high molecular weight polyethylene fiber as well as preparation method and application thereof
Through multi-stage stretching and acid bath treatment, porous ultra-high molecular weight polyethylene fibers are formed, which solves the problems of smooth surface of the fiber and inert molecular structure, and realizes the moisture conduction and softness of the fibers. It is suitable for clothing and home textiles and other fields, and improves the peel strength and color fastness of the composite materials.
Patent Information
- Application Number
- CN202311153947.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
Ultra-high molecular weight polyethylene fibers have smooth surfaces and inert molecular structures, making it difficult to compound with organic colloids, resulting in low peeling strength of composite materials, and are not soft, does not guide wet, has poor touch, is difficult to paint, and has low color fastness in home textile applications.
By mixing ultra-high molecular weight polyethylene, acid soluble inorganic particles and solvents into a spinning liquid, extrude to form a spinning stream, remove some solvents to form dry raw silk, perform multi-stage stretching, and dissolve acid soluble inorganic particles in an acid bath to form porous ultra-high molecular weight polyethylene fibers.
It realizes the distribution of micro-nano-scale pores on the surface and inside of the fiber, enhances the moisture conduction and softness of the fiber, is suitable for the fields of clothing and home textiles, and improves the peel strength and color fastness of the composite material.
Smart Images

Figure BDA0004437875460000171
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high-performance fibers, and in particular to a porous ultra-high molecular weight polyethylene fiber, a manufacturing method thereof and applications thereof. Background Art
[0002] As the most industrialized high-performance fiber, ultra-high molecular weight polyethylene fiber has been widely used in military bulletproof, aerospace, marine industry and other fields. In order to meet the needs of more and more fields, people have gradually shifted from the research and development of fiber production to modified fiber. Among them, in order to overcome the problems of single molecular structure, strong chemical inertness, smooth surface and difficulty in compounding of ultra-high molecular weight polyethylene fiber, people began to develop porous ultra-high molecular weight polyethylene fiber.
[0003] Patent CN101205633A discloses a method for preparing a porous hollow high-strength high-modulus ultra-high molecular weight polyethylene fiber, which is made by a slit spinneret and a wet spinning process. Patent CN108004605A discloses a medium-strength porous ultra-high molecular weight polyethylene fiber and a preparation method, which is made by wet spinning and forming holes through an extraction solvent, and is used for uranium extraction from seawater, etc. Patent CN104746165A discloses an ultra-high molecular weight polyethylene porous fiber and a preparation method thereof, which is made by wet spinning to form a fiber with a porosity of 23.60%-58.99%, and is used for uranium extraction from seawater and water-absorbing materials. Patent CN112323158A discloses a method for preparing a porous active ultra-high molecular weight polyethylene fiber, polyethylene fiber and its use, which uses water to dissolve inorganic salts such as sodium chloride to form holes during the hot drawing process, and is used for cement composite fibers. Summary of the invention
[0004] In the prior art, ultra-high molecular weight polyethylene fibers have a smooth surface and an inert molecular structure, making them difficult to compound with organic colloids. The resulting composite materials have low peel strength, especially when used in high-pressure scenarios, such as high-pressure airbags, which can cause peeling failure. On the other hand, ultra-high molecular weight polyethylene fibers in the prior art have a dense structure, an inert molecular structure, do not absorb water, and have a high modulus. Therefore, in clothing and home textile applications, they are not soft, do not conduct moisture, have a poor touch, are not easy to color, and have low color fastness. The present invention provides an ultra-high molecular weight polyethylene fiber with holes, which can solve the problem that the surface of ultra-high molecular weight polyethylene fibers is smooth and not easy to adsorb and compound. On the other hand, it can provide a good soft and moisture-conducting effect for clothing and home textile fabrics.
[0005] Specifically, the present invention relates to the following aspects.
[0006] 1. A method for producing porous ultra-high molecular weight polyethylene fiber, comprising the following steps:
[0007] 1) mixing ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent to prepare a spinning solution,
[0008] 2) extruding the spinning solution to form a spinning fine stream,
[0009] 3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers,
[0010] 4) stretching the dry raw yarn in one or more stages (e.g., 2-10 or 2-6 stages) to obtain pre-drawn yarn,
[0011] 5) The pre-drawn filaments are immersed in an acid bath under ultrasonic or non-ultrasonic conditions to dissolve the acid-soluble inorganic particles, thereby obtaining the porous ultra-high molecular weight polyethylene fibers.
[0012] 2. The manufacturing method described in any of the preceding or following aspects, wherein in step 1), the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene, and the amount of the solvent is 100-3000 parts by weight (preferably 200-400 parts by weight).
[0013] 3. The production method described in any of the preceding or following aspects, wherein in step 1), the solvent is selected from at least one of white oil, mineral oil, naphthalene, decalin, tetralin, kerosene, xylene, toluene, petroleum fractions, halogenated hydrocarbons, cycloalkanes, and cycloolefins, preferably decalin.
[0014] 4. The production method described in any one of the preceding or following aspects, wherein in step 1), the average particle size of the acid-soluble inorganic particles is 0.02-50 μm (preferably 0.5-5 μm).
[0015] 5. The manufacturing method described in any of the preceding or following aspects, wherein in step 1), the acid-soluble inorganic particles are selected from at least one particle of calcium carbonate, sodium carbonate, sodium bicarbonate, and magnesium carbonate (preferably calcium carbonate particles, especially light calcium carbonate particles).
[0016] 6. The method of any one of the preceding or following aspects, wherein in step 1), the difference between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.10 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ).
[0017] 7. The manufacturing method described in any of the above or the following aspects, wherein in step 1), the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).
[0018] 8. The manufacturing method described in any one of the preceding or following aspects, wherein in step 1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.
[0019] 9. The manufacturing method described in any of the above or the following aspects, wherein in step 2), stretching exists or does not exist, and the extrusion temperature is 150-250°C (preferably 170-190°C); when stretching exists, the stretching ratio is 0-50 (preferably 2-20).
[0020] 10. The manufacturing method according to any one of the preceding or following aspects, wherein in step 3), at least a portion of the solvent is removed from the spinning stream by evaporation.
[0021] 11. The manufacturing method described in any of the above or the following aspects, wherein in step 3), the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0022] 12. The manufacturing method according to any one of the preceding or following aspects, wherein in step 3), the spinning stream is cooled to obtain gel filaments, and then at least a portion of the solvent is removed by evaporation and / or extraction.
[0023] 13. The manufacturing method described in any of the above or the following aspects, wherein the cooling operating conditions include: with or without stretching, the cooling temperature is -50-100°C (preferably 20-50°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0024] 14. The manufacturing method described in any of the above or the following aspects, wherein the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching is present, the stretching ratio is 1-10 (preferably 2-5), or, the operating conditions of the extraction include: with or without stretching, the extractant is a volatile hydrocarbon solvent (preferably selected from at least one of xylene and heptane), the extraction temperature is 10-150°C (preferably 40-90°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0025] 15. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), the stretching operating conditions include: 1-10 stretching sections (preferably 2-5), a stretching temperature of 90-170°C (preferably 130-150°C), and a stretching ratio of 2-500 (preferably 4-250).
[0026] 16. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), the dry raw silk is first pre-stretched, and then further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio of the post-stretching (total) is 2-50 (preferably 5-20).
[0027] 17. The manufacturing method described in any of the preceding or following aspects, wherein there is no stretching during step 5), or there is no stretching operation after step 5).
[0028] 18. The production method according to any one of the preceding or following aspects, wherein in step 5), the acidic bath comprises at least one acid selected from inorganic acids and organic acids, and a solvent.
[0029] 19. The manufacturing method described in any of the preceding or following aspects, wherein the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid, and phosphoric acid (preferably selected from at least one of sulfuric acid and hydrochloric acid), the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid (preferably selected from at least one of acetic acid and citric acid), and the solvent is selected from at least one of glacial acetic acid, ethanol, and water, preferably water.
[0030] 20. The production method according to any one of the preceding or following aspects, wherein the pH value of the acidic bath is ≤ 6.5 (preferably 2-3).
[0031] 21. The manufacturing method described in any of the above or the following aspects, wherein in step 5), the dissolution operating conditions include: the dissolution temperature is 0-80°C (preferably 20-40°C), the dissolution time is 0.5-60min (preferably 10-20min), and when there is ultrasonic oscillation, the frequency is 10-70Hz (preferably 30-40Hz).
[0032] 22. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), an oil is applied to the dry raw silk before the stretching is performed and / or between any two stages.
[0033] 23. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), an oil is applied to the dry raw silk before the post-stretching is performed and / or between any two stages (if any) of the post-stretching.
[0034] 24. The production method described in any of the above or below aspects, wherein the oil agent is selected from at least one of glycerides, mineral oils, lauryl alcohol polyoxyethylene ethers, and antistatic agents, preferably glycerides.
[0035] 25. The production method described in any of the preceding or following aspects, wherein the amount of the oil agent used is 0-10% (preferably 0.1-3%).
[0036] 26. A porous ultra-high molecular weight polyethylene fiber obtained by the production method described in any one of the preceding or following aspects.
[0037] 27. The polyethylene fiber described in any of the preceding or following aspects has a porosity of 5-40% (preferably 10-20%) and a fiber strength of 10-40 cN / dtex (preferably 15-25 cN / dtex).
[0038] 28. A fabric comprising the porous ultra-high molecular weight polyethylene fiber described in any one of the preceding or following aspects or the porous ultra-high molecular weight polyethylene fiber produced by the production method described in any one of the preceding or following aspects.
[0039] 29. The fabric described in any one of the preceding or following aspects further comprises at least one other fiber selected from natural plant fibers, natural animal fibers, artificial regenerated fibers, synthetic fibers and inorganic fibers.
[0040] Technical Effects
[0041] The porous ultra-high molecular weight polyethylene fiber of the present invention has micro-nano-scale pores distributed on the surface and inside, which ensures the integrity of the fiber as much as possible, makes the fiber more moisture-conductive, maintains the cool feeling of the fiber and is comfortable and breathable. The pore structure is easy to color and retains color, and is suitable for knitting fields such as clothing and home textiles. The pore structure is easy to adsorb, and is suitable for making composite materials and adsorption materials. DETAILED DESCRIPTION
[0042] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.
[0043] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0044] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0045] In the context of the present invention, all numerical values for parameters (eg amounts or conditions) are to be understood as being modified in all instances by the term "about", regardless of whether "about" actually appears before the numerical value.
[0046] In the context of the present invention, the method for measuring porosity is mercury intrusion porosimetry.
[0047] In the context of the present invention, the fiber strength is measured according to GB / T19975-2005.
[0048] In the context of the present invention, the method of measuring the average particle size is laser scattering.
[0049] In the context of the present invention, the peel strength is tested according to FZ / T 60011-2016, the color fastness to rubbing is tested according to GB / T3920-2008, and the color fastness to soaping is tested according to GB / T3921-2008.
[0050] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight and pressure is gauge pressure.
[0051] In the context of the present invention, any two or more embodiments or aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0052] According to one embodiment of the present invention, a method for manufacturing a porous ultra-high molecular weight polyethylene fiber comprises the following steps:
[0053] 1) mixing ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent to prepare a spinning solution,
[0054] 2) extruding the spinning solution to form a spinning fine stream,
[0055] 3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers,
[0056] 4) stretching the dry raw yarn in one or more stages (e.g., 2-10 or 2-6 stages) to obtain pre-drawn yarn,
[0057] 5) The pre-drawn filaments are immersed in an acid bath under ultrasonic or non-ultrasonic conditions to dissolve the acid-soluble inorganic particles, thereby obtaining the porous ultra-high molecular weight polyethylene fibers.
[0058] According to one embodiment of the present invention, the ultra-high molecular weight polyethylene, the antioxidant (optional), the acid-soluble inorganic particles and the solvent are put into a swelling kettle, swollen, homogenized, and prepared into a spinning suspension. Then, the spinning suspension is sheared, dissolved and extruded by a screw to form a spinning stream. Then, the spinning stream can be formed into a dry precursor in two ways: 1) the spinning stream is directly dried to remove the solvent to form a dry precursor; 2) the spinning stream enters a coagulation bath to cool and coagulate into a gel pre-drawn filament, and then the solvent is removed by extraction or drying to form a dry precursor.
[0059] According to one embodiment of the present invention, in step 1), the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene.
[0060] According to one embodiment of the present invention, in step 1), the amount of the solvent used is 100-3000 parts by weight (preferably 200-400 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene.
[0061] According to one embodiment of the present invention, in step 1), the solvent is selected from at least one of white oil, mineral oil, naphthalene, decalin, tetralin, kerosene, xylene, toluene, petroleum fractions, halogenated hydrocarbons, cycloalkanes, and cycloolefins, preferably decalin.
[0062] According to one embodiment of the present invention, in step 1), the average particle size of the acid-soluble inorganic particles is 0.02-50 μm (preferably 0.5-5 μm).
[0063] According to one embodiment of the present invention, in step 1), the acid-soluble inorganic particles are not particularly limited, and may be any inorganic particles that can react chemically with an acid (particularly hydrochloric acid or a hydrochloric acid aqueous solution) to be converted into (water) soluble compounds, and in particular may be at least one particle selected from calcium carbonate, sodium carbonate, sodium bicarbonate and magnesium carbonate, preferably calcium carbonate particles, in particular light calcium carbonate particles (whose bulk density is generally 0.50-0.70 g / cm 3 ).
[0064] According to one embodiment of the present invention, in order to make the technical effect of the present invention more excellent, in step 1), the difference (absolute value) between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.10 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ). Preferably, the relative density of the ultra-high molecular weight polyethylene is greater than the bulk density of the acid-soluble inorganic particles. It is known that the relative density of the ultra-high molecular weight polyethylene is generally 0.90-0.97 g / cm 3 .
[0065] According to one embodiment of the present invention, in step 1), the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).
[0066] According to one embodiment of the present invention, in order to make the technical effect of the present invention more excellent, in step 1), the acid-soluble inorganic particles are mixed with the solvent, and then mixed with the ultra-high molecular weight polyethylene.
[0067] According to one embodiment of the present invention, in step 2), stretching may or may not be performed, and the extrusion temperature is 150-250° C. (preferably 170-190° C.); when stretching is performed, the stretching ratio is 0-50 (preferably 2-20).
[0068] According to one embodiment of the present invention, in step 3), at least a portion of the solvent is removed from the spinning stream by evaporation (direct evaporation desolvation method). According to the present invention, except for the following clear operating conditions, there is no other limitation on the direct evaporation desolvation method, and it can be carried out in a manner conventionally known in the art. Here, the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature. When stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0069] According to one embodiment of the present invention, in step 3), the spinning stream is cooled to obtain gel filaments (gel spinning method), and then at least a portion of the solvent is removed by evaporation and / or extraction. According to the present invention, except for the following clear operating conditions, there is no other limitation for the gel spinning method, and it can be carried out in a conventional manner known in the art.
[0070] According to one embodiment of the present invention, the cooling operation conditions include: with or without stretching, the cooling temperature is -50-100°C (preferably 20-50°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0071] According to one embodiment of the present invention, the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching exists, the stretching ratio is 1-10 (preferably 2-5).
[0072] According to one embodiment of the present invention, the operating conditions of the extraction include: with or without stretching, the extractant is a volatile hydrocarbon solvent, the extraction temperature is 10-150°C (preferably 40-90°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5). Here, as the volatile hydrocarbon solvent, for example, at least one of xylene and heptane can be cited.
[0073] According to one embodiment of the present invention, in step 4), the stretching operating conditions include: 1-10 stretching sections (preferably 2-5), a stretching temperature of 90-170°C (preferably 130-150°C), and a stretching ratio of 2-500 (preferably 4-250).
[0074] According to one embodiment of the present invention, in step 4), the dry raw silk is first pre-stretched, and then further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio of the post-stretching (total) is 2-50 (preferably 5-20).
[0075] According to one embodiment of the present invention, there is no stretching during step 5), or there is no stretching operation after step 5).
[0076] According to one embodiment of the present invention, in step 5), the acid bath comprises at least one acid selected from inorganic acids and organic acids, and a solvent.
[0077] According to one embodiment of the present invention, the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid and phosphoric acid, preferably selected from at least one of sulfuric acid and hydrochloric acid, especially hydrochloric acid.
[0078] According to one embodiment of the present invention, the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid, preferably selected from at least one of acetic acid and citric acid.
[0079] According to one embodiment of the present invention, the solvent is selected from at least one of glacial acetic acid, ethanol and water, preferably water.
[0080] According to one embodiment of the present invention, the pH value of the acidic bath is ≤6.5 (preferably 2-3).
[0081] According to one embodiment of the present invention, in step 5), the dissolution operating conditions include: a dissolution temperature of 0-80°C (preferably 20-40°C), a dissolution time of 0.5-60 min (preferably 10-20 min), and an ultrasonic oscillation frequency of 10-70 Hz (preferably 30-40 Hz).
[0082] According to one embodiment of the present invention, in step 4), an oil is applied to the dry raw silk before the stretching and / or between any two stages. Alternatively, an oil is applied to the dry raw silk before the post-stretching and / or between any two stages (if any) of the post-stretching. According to the present invention, since the surface of the fiber to which the peracid-soluble inorganic particles are added is rough, it is easy to wear and cause powder loss or fiber surface damage during the subsequent drawing process, and oil film protection is generally required.
[0083] According to one embodiment of the present invention, the oil agent is selected from at least one of glycerides, mineral oils, lauryl alcohol polyoxyethylene ethers, and antistatic agents, preferably glycerides.
[0084] According to one embodiment of the present invention, the amount of the oil agent is 0-10% (preferably 0.1-3%).
[0085] According to one embodiment of the present invention, it also relates to a porous ultra-high molecular weight polyethylene fiber obtained by the manufacturing method described above in the present invention.
[0086] According to one embodiment of the present invention, the porosity of the polyethylene fiber is 5-40% (preferably 10-20%).
[0087] According to one embodiment of the present invention, the fiber strength of the polyethylene fiber is 10-40 cN / dtex (preferably 15-25 cN / dtex).
[0088] According to one embodiment of the present invention, there is also a fabric, which comprises the porous ultra-high molecular weight polyethylene fiber described above in the present invention or the porous ultra-high molecular weight polyethylene fiber manufactured by the manufacturing method described above in the present invention. According to the present invention, as the fabric, a composite fabric is made, the peeling strength is ≥ 20N / m, and the color fastness to friction and the color fastness to soaping reach level 5.
[0089] According to one embodiment of the present invention, the fabric further comprises at least one other fiber selected from natural plant fibers, natural animal fibers, artificial regenerated fibers, synthetic fibers and inorganic fibers.
[0090] Example
[0091] The present invention is further described in detail below using examples and comparative examples, but the present invention is not limited to these examples.
[0092] Example 1
[0093] The porous ultra-high molecular weight polyethylene fiber of this embodiment is obtained by the following process:
[0094] The acid-soluble inorganic particles are light calcium carbonate, and the difference between the bulk density and the relative density of ultra-high molecular weight polyethylene is 0.4g / cm 3 , with an average particle size of 1 μm. After being mixed and dispersed evenly with decahydronaphthalene solvent, it is mixed with ultra-high molecular weight polyethylene to form a swelling suspension. The mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: decahydronaphthalene is 100:2:1300. The suspension is sheared and dissolved by a screw, and extruded at 180°C and 8 times stretching to form a spinning fine flow. The solvent is removed by direct evaporation, the evaporation temperature is 3°C higher than the flash temperature of decahydronaphthalene, and the stretching ratio is 3. This step removes at least 95% of the solvent residue. Then it passes through 3 stretching sections, the stretching temperature is 140-147°C, the stretching ratio is 20, and then it passes through a dilute hydrochloric acid bath (hydrochloric acid and water) with a pH of 3, the stretching ratio in the bath is 1.45, and it is ultrasonically oscillated at 30°C and 30Hz, dissolved for 15 minutes, and then oiled by a tanker with an oiling ratio of 0.5%, and finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 17.8% and the fiber strength is 24.43cN / dtex after mercury intrusion testing. The fiber is woven into plain cloth and compounded with polyurethane material. The peel strength is 60.51N / m. After the fiber is dipped in glue and knitted into cloth, the color fastness to friction and soap washing reaches level 5.
[0095] Example 2
[0096] Same as Example 1, except that the acid-soluble inorganic particles are heavy calcium carbonate, and the difference between its bulk density and the relative density of ultra-high molecular weight polyethylene is 0.27 g / cm 3 . This embodiment finally forms 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 13.5% and the fiber strength is 23.12 cN / dtex after mercury intrusion testing. The prepared fiber is woven into plain cloth and compounded with polyurethane material. The peel strength is tested to be 45.02 N / m. After the fiber is dipped in glue and colored and knitted into cloth, the color fastness to friction and soap washing reaches level 5.
[0097] Example 3
[0098] Same as Example 1, except that the acid-soluble inorganic particles are sodium carbonate, and the difference between the bulk density and the relative density of ultra-high molecular weight polyethylene is 0.30 g / cm 3. This embodiment finally forms 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 14.21% and the fiber strength is 25.08cN / dtex as tested by mercury intrusion method. The prepared fiber is woven into plain cloth and compounded with polyurethane material. The peel strength is tested to be 46.32N / m. After the fiber is dipped in glue and colored and knitted into cloth, the color fastness to friction and soap washing reaches level 5.
[0099] Example 4
[0100] The same as Example 1, except that calcium carbonate is not premixed with the solvent, but directly mixed with the ultra-high molecular weight polyethylene and the solvent. This example finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 8.3% and the fiber strength is 16.71 cN / dtex as tested by mercury intrusion. The prepared fiber is woven into a plain cloth and composited with a polyurethane material. The peel strength is tested to be 30.05 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is level 4, and the color fastness to soaping reaches level 4.
[0101] Example 5
[0102] The same as Example 1, except that it does not go through 3 stretching sections, but through 1 stretching section, the stretching temperature is 155°C, and the stretching ratio is 13. This example finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 5.6% and the fiber strength is 13.47cN / dtex tested by mercury intrusion. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 27.34N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 4, and the color fastness to soaping reaches 4.
[0103] Example 6
[0104] The same as Example 1, except that there is no drafting in the bath. This example finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 11.2% and the fiber strength is 18.73 cN / dtex as tested by mercury intrusion method. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 40.12 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 4, and the color fastness to soaping reaches 4.
[0105] Example 7
[0106] Same as Example 1, except that citric acid is used, pH=6.0. This example finally forms 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 10.2% and the fiber strength is 22.15 cN / dtex as tested by mercury intrusion method. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 37.82 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 4, and the color fastness to soaping reaches 4.
[0107] Example 8
[0108] The same as Example 1, except that the method of direct evaporation and solvent removal is not adopted, but the gel method is adopted, the cooling temperature is 30°C, the stretch ratio during cooling is 2.7, and then the solvent is evaporated, and the process is the same as Example 1. This embodiment finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 15.0% and the fiber strength is 24.15 cN / dtex tested by mercury intrusion. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peeling strength is tested to be 59.23 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 5 levels, and the color fastness to soaping reaches 5 levels.
[0109] Example 9
[0110] The same as Example 1, except that white oil is used as a solvent, the mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: white oil is 100:2:1400, the cooling temperature is 25°C, the stretch ratio during cooling is 3.0, xylene extraction is used, the extraction temperature is 50°C, and the extraction stretch ratio is 2.1. This embodiment finally forms a 400D porous ultra-high molecular weight polyethylene fiber. Tested by mercury intrusion method, the porosity is 12.8%, and the fiber strength is 20.06cN / dtex. The prepared fiber is woven into a plain cloth and composited with a polyurethane material. The tested peel strength is 35.28N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is level 4, and the color fastness to soaping reaches level 4.
[0111] Example 10
[0112] The same as Example 1, except that the mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: decalin is 100: 20: 1300. This example finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 25.0% and the fiber strength is 8.81 cN / dtex as tested by mercury intrusion method. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 23.15 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is level 3, and the color fastness to soaping reaches level 4.
[0113] Embodiment 11
[0114] Same as Example 1, except that the acid-soluble inorganic particles are a mixture of heavy calcium carbonate and light calcium carbonate, and the difference between the bulk density and the relative density of ultra-high molecular weight polyethylene is 0.20 g / cm 3 . This embodiment finally forms 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 9.5% and the fiber strength is 10.23 cN / dtex after mercury intrusion testing. The prepared fiber is woven into plain cloth and compounded with polyurethane material. The peel strength is tested to be 32.17 N / m. After the fiber is dipped in glue and colored and knitted into cloth, the color fastness to friction is level 4 and the color fastness to soap washing reaches level 4.
[0115] Example 12
[0116] Same as Example 1, except that the acid-soluble inorganic particles are magnesium carbonate, and the difference between its bulk density and the relative density of ultra-high molecular weight polyethylene is 0.65 g / cm 3 . This embodiment finally forms 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 10.6% and the fiber strength is 7.81cN / dtex after mercury intrusion testing. The prepared fiber is woven into plain cloth and compounded with polyurethane material. The peel strength is tested to be 36.25N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 4, and the color fastness to soap washing reaches 4.
[0117] Embodiment 13
[0118] The same as Example 1, except that the evaporation temperature is 5°C higher than the flash temperature of decalin, the stretching ratio is 5, and this step removes at least 98% of the solvent residue. This embodiment finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 15.32% and the fiber strength is 24.71cN / dtex tested by mercury intrusion. The prepared fiber is woven into a plain cloth and composited with a polyurethane material. The peel strength is tested to be 42.31N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is level 5, and the color fastness to soaping reaches level 5.
[0119] Embodiment 14
[0120] The same as Example 1, except that dilute sulfuric acid is used, pH = 2.0. This example finally forms 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 18.9% and the fiber strength is 23.28 cN / dtex as tested by mercury intrusion method. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 53.31 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 5, and the color fastness to soaping reaches 5.
[0121] Embodiment 15
[0122] The same as Example 1, except that it does not go through 3 stretching sections, but through 5 stretching sections, the stretching temperature is 145°C, and the stretching ratio is 20. This example finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 16.8% and the fiber strength is 22.38cN / dtex tested by mercury intrusion. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 41.23N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is 5, and the color fastness to soaping reaches 5.
[0123] Comparative Example 1
[0124] The fiber is commercially available LY25 400D ultra-high molecular weight polyethylene fiber.
[0125] Comparative Example 2
[0126] The same as Example 1, except that it is first passed through a dilute hydrochloric acid bath (hydrochloric acid and water) with a pH of 3, the stretching ratio in the bath is 1.45, ultrasonic oscillation is applied at 30°C and 30Hz, and the solution is dissolved for 15 minutes, and then passed through 3 stretching sections, the stretching temperature is 140-147°C, and the stretching ratio is 20. This embodiment finally forms a 400D porous ultra-high molecular weight polyethylene fiber. Tested by mercury intrusion, the porosity is 4.3% and the fiber strength is 18.23cN / dtex. The prepared fiber is woven into a plain cloth and compounded with a polyurethane material, and the tested peel strength is 20.12N / m. After the fiber is dipped in glue and colored and knitted into cloth, the color fastness to friction is level 2, and the color fastness to soaping reaches level 3.
[0127] Comparative Example 3
[0128] The same as Example 1, except that light calcium carbonate is replaced by sodium chloride. This example finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity is 3.7% and the fiber strength is 14.58 cN / dtex as tested by mercury intrusion. The prepared fiber is woven into plain cloth and composited with polyurethane material. The peel strength is tested to be 19.23 N / m. After the fiber is dipped in glue and colored, and knitted into cloth, the color fastness to friction is level 2, and the color fastness to soaping reaches level 3.
[0129] Comparative Example 4
[0130] The same as Example 1, except that the acid bath is first used for dipping and then the solvent is removed. In this example, too many broken fibers can not form effective finished fibers.
[0131]
Claims
1. A method for producing porous ultra-high molecular weight polyethylene fiber, comprising the following steps: 1) mixing ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent to prepare a spinning solution, 2) extruding the spinning solution to form a spinning fine stream, 3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers, 4) stretching the dry raw yarn in one or more stages (e.g., 2-10 or 2-6 stages) to obtain pre-drawn yarn, 5) The pre-drawn filaments are immersed in an acid bath under ultrasonic or non-ultrasonic conditions to dissolve the acid-soluble inorganic particles, thereby obtaining the porous ultra-high molecular weight polyethylene fibers.
2. The manufacturing method according to claim 1, wherein in step 1), the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene, and the amount of the solvent is 100-3000 parts by weight (preferably 200-400 parts by weight).
3. The manufacturing method according to claim 1, wherein in step 1), the difference between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.10 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ).
4. The production method according to claim 1, wherein in step 1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.
5. The manufacturing method according to claim 1, wherein in step 2), stretching is present or absent, and the extrusion temperature is 150-250°C (preferably 170-190°C); when stretching is present, the stretching ratio is 0-50 (preferably 2-20).
6. The manufacturing method according to claim 1, wherein in step 3), at least a portion of the solvent is removed from the spinning stream by evaporation, or the spinning stream is cooled to obtain gel filaments, and then at least a portion of the solvent is removed by evaporation and / or extraction.
7. The manufacturing method according to claim 1, wherein in step 4), the operating conditions of the stretching include: The number of stretching sections is 1-10 (preferably 2-5), the stretching temperature is 90-170° C. (preferably 130-150° C.), and the stretching ratio is 2-500 (preferably 4-250).
8. The manufacturing method of claim 1, wherein in step 4), the dry raw silk is first pre-stretched, and then further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio of the post-stretching (total) is 2-50 (preferably 5-20).
9. The manufacturing method according to claim 1, wherein there is no stretching during the step 5), or there is no stretching operation after the step 5).
10. The production method according to claim 1, wherein in step 5), the acid bath comprises at least one acid selected from inorganic acids and organic acids, and a solvent.
11. The production method according to claim 10, wherein the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid, and phosphoric acid (preferably selected from at least one of sulfuric acid and hydrochloric acid), the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid (preferably selected from at least one of acetic acid and citric acid), and the solvent is selected from at least one of glacial acetic acid, ethanol, and water, preferably water.
12. The manufacturing method according to claim 1, wherein in step 5), the dissolving operating conditions include: The pH value of the acid bath is ≤6.5 (preferably 2-3), the dissolution temperature is 0-80°C (preferably 20-40°C), the dissolution time is 0.5-60min (preferably 10-20min), and when there is ultrasonic oscillation, the frequency is 10-70Hz (preferably 30-40Hz).
13. The manufacturing method according to claim 1, wherein in step 4), an oil is applied to the dry raw silk before the stretching is performed and / or between any two stages.
14. The manufacturing method according to claim 1, wherein in step 4), an oil is applied to the dry raw silk before the post-drawing is performed and / or between any two stages (if any) of the post-drawing.
15. A porous ultra-high molecular weight polyethylene fiber obtained by the production method according to claim 1.
16. The polyethylene fiber according to claim 15, which has a porosity of 5-40% (preferably 10-20%) and a fiber strength of 10-40 cN / dtex (preferably 15-25 cN / dtex). 17 . A fabric comprising the porous ultra-high molecular weight polyethylene fiber according to claim 15 or the porous ultra-high molecular weight polyethylene fiber produced by the production method according to claim 1 .
Citation Information
Patent Citations
Method for preparing porous hollow high-strength high-modulus super-high molecular weight polyethylene fibre
CN101205633A
Ultra-high molecular weight polyethylene porous fiber and preparation method thereof
CN104746165A
Non-breakpoint direct spinning continuous production method of ultra-high molecular weight polyethylene fiber
CN101798711A
Medium-strength porous ultrahigh molecular weight polyethylene fiber and preparation method
CN108004605A
Preparation method of porous active ultra-high molecular weight polyethylene fiber, polyethylene fiber and application of polyethylene fiber
CN112323158A